Effectiveness of digital module development in Pancasila education learning using the Flip PDF Professional application - Reinita, Reinita; Putri, Amelisa (Universitas Negeri Yogyakarta, 2024)
This research was motivated by the fact that the use of printed textbooks in elementary schools was not able to increase student activity, motivation, and participation. The teacher's teaching materials do not yet use Flip PDF Professional. This research aims to produce a computerized module using Flip PDF Professional as a Pancasila Education teaching application. The research method used is research and development. The type of research is research and development using 4D. This 4D model, namely: defining, designing, developing, and disseminating. The research subjects were 22 fourth-grade students at Bukit Cangang Elementary School 12, 24 students at ATTS Elementary School 14 at meeting 1 and 25 students at meeting 2, as well as 18 students at Benteng Elementary School 01 at meeting 1 and 21 students at meeting 2. The digital module was declared effective after an effectiveness test was carried out. At meeting 1 on the topic of rules at home and rules at school, students obtained a completion result with a percentage of 86% and for meeting 2, on the topic of rules in the surrounding environment, students obtained a completion result with a percentage of 88%. These results provide digital module development with effective results for use. Thus, it can also be said that the digital module that supports the Flip PDF Professional application in elementary class IV schools is very significant, very easy to use, and very useful for teaching.